The dynamic of discriminatory reform: How does discretionary pricing neutralize the productivity gains of energy subsidy reform in Iran? - Ali Hojati Najafabadi; Mohammad Rahmati; Seyed Ali Madanizadeh (Journal of Applied Economics, 2023)
A distortion caused by previous policies could distort the results of reforms. This may explain why policies to reduce industrial fuel subsidies have not necessarily resulted in increases in aggregate productivity in countries with mandated pricing. To identify and measure these distortions' effects, we estimate a structural dynamic firm model with endogenous technology adaptation using data from the manufacturing firms in Iran. By connecting two price distortions and their results on the real sector, results suggest significant room for a distributional policy. We estimated dispersion elasticity comparable to the price elasticity of energy consumption in the manufacturing sector. Results suggest that the intensive margin is the primary driver of energy price elasticity, whereas the other channels mostly offset it. Moreover, total factor productivity slightly improves in light of a reduction in energy consumption if, at the same time, the redistribution policy boosts the aggregate demands.
Keywords: 330; Energy reform; firm dynamics; structural estimation; subsidy policy